Manajemen Sarana dan Prasarana Pendidikan di Sekolah Menengah Kejuruan pada Pondok Pesantren (Institut Agama Islam Negeri Kendari, 2023)
This qualitative study aims to examine the planning, procurement, distribution, inventory and maintenance of educational facilities and infrastructure at a vocational high school of an Islamic boarding school in Kendari. Data were gathered through observation, interview and documentation methods. The results of data analysis indicate that the school facilities and infrastructure management comprises of planning which is adjusted to the needs, procurement from various funding, and keeping inventory books. The findings also reveal that the distribution and use of facilities and infrastructure is managed by the school principal and teachers, while the maintenance is carried out routinely by having a daily maintenance by the students and periodic maintenance by technicians and those in charge of the laboratory.Keywords:Â Islamic boarding school; facilities and infrastructure; management; vocational high school